International Business in the Information and Digital Age. - van Tulder, Rob.; Verbeke, Alain; Piscitello, Lucia; ProQuest (firma) (Bingley : Emerald Publishing Limited, 2018)
The information and digital age is shaped by a smallnumber of multinational enterprises from a limited number of countries. Thisvolume covers the latest insight from the International Business discipline onprevailing trends in business model evolution. It also discusses criticalissues of regulation in the new information and digital space..
5.3. Expectations Regarding the Impact of Smart Services on International (Service) Business -- 6. Discussion of Findings -- 6.2. The Ability of Smart Services to Improve Firms' Grip on the Installed Base -- 6.2.1 Obstacles to Keeping a Grip on the Installed Base -- 6.2.2. Facilitators to Keeping a Grip on the Installed Base -- 6.3. The Impact of Smart Services on International (Service) Business -- 6.3.1. Exploiting the Current Captive Market and Deepening Current Customer Relationships -- 6.3.2. Landing New Customers in Existing Markets Through More Competitive Offerings -- 6.3.3. Exploring New Markets and Diversifying Current Customer Relationships -- 6.3.4. Generating Value from Service Business Development -- 6.4. Interpretation of the Findings in the Light of Hidden Champions' Specific Features -- 6.4.1. Use of Complementary Assets -- 6.4.2. Centrality of Supplied Assets in the User's Value-Creation Processes -- 7. Concluding Remarks -- References -- Chapter 12: Additive Manufacturing and Global Value Chains: An Empirical Investigation at the Country Level -- 1. Introduction -- 2. AM Technologies and Their Applications: The State of the Art -- 3. AM and GLOBAL VALUE CHAINS -- 3.1. AM, Economies of Scale, Production Stages and GVCs -- 3.2. AM, Skill Intensity and GVCs -- 4. Data and Descriptive Statistics on AM Patenting and GLOBAL VALUE CHAINS -- 4.2. GVCs Indicators -- 5. Empirical Evidence -- 5.1. Data, Empirical Strategy and Methodology -- 6. Econometric Findings -- 7. Conclusions -- References -- Part IV: Industry 4.0 -- Chapter 13: Amazon and Alibaba: Internet Governance, Business Models, and Internationalization Strategies -- 1. Introduction -- 2. Conceptual Framework -- 2.1. Firm Typologies and Business Models in the Digital Economy -- 2.2. Internationalization Strategies and Home Country -- 3. Methodology -- 4. Findings.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2019. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: International business enterprises-Technological innovations..; International business enterprises-Data processing; elektronické knihy; electronic books